Development of an Automated Selection System for Cutting Tools and Machining Parameters of Milling Operations - Goay, Lay Nee (2005)
This project deals with development of a cutting tools and machining parameter selection system for milling processes and named TnP system. The developed system has been divided into six modules. The first and second modules are concerned with blank and machine selection. The third module deals with feature descriptions with some basic dimensioning functioned as input to automate operation selection in the fourth module. The fifth and sixth modules are regarding the cutting tools selection, cutting parameters selection and generation of process plan sheet. The whole system is developed by using Visual Basic.net as Graphical User Interface (GUI) and Structure Query Language server (SQL server) as supporting data storage and retrieval system. The integration of user interface and database has been implemented using program coding written in Visual Basic.The specialty of the developed system is that it automates the selection of cutting tools and cutting conditions of milling operations. In addition, the user or process planner is able to modify and enhance the generated result from the system to meet their individual requirements. A test run has been included to demonstrate the potential and application of the developed system.